Resolution of matrimonial dispute in the Civil Court of Malaysia: Mediation as away forward - Ibrahim, Norliah; Abdul Hak, Nora (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
In the system of justice, techniques for resolving family disputes are either negotiation or litigation. It is however, seen to have minimized the importance of negotiation and exaggerated the importance of litigation. It has been commented that lawyers have not fully explored other alternatives to litigation such as, mediation, conciliation and medarb. Many jurisdictions around the world have introduced ADR processes in their legal systems such as Singapore, Australia, New Zealand and United States. In Malaysia, the Malaysian Judiciary Department has introduced Practice Direction No. 10 of 2010 as an effort to encourage mediation in the Civil Court among lawyers and judges. As the nature of many family disputes is self-assertion and compromise, negotiation is developing to be a primary method for resolving conflicts within the family environment. Thus, mediation, as one of the important mechanisms of negotiation, has great potential to resolve family disputes, one of which is matrimonial property dispute. There may be disagreements between the parties over division of property during or after divorce. This type of dispute may be settled using goal-oriented mediation process so that further conflict can be avoided. This paper aims to discuss the use of mediation in resolving matrimonial property dispute by looking at the nature of mediation, its advantages and disadvantages; the present relevant law relating to mediation and its practice in Malaysia. Data for this write up was obtained from materials consisting of textbooks, decided cases, legislation, journals, newspapers, seminar and conference papers and unpublished writings (dissertations and theses). This paper involves investigation and analysis of the materials available in the library hence, it uses a legal analytical approach. This paper is a preamble to a more detailed study of the use of mediation in matrimonial dispute which hopefully the suggestions/obsevations made will be useful for further improvement of the existing legal provision and practice in Malaysia